The Noblest Roman of them All. - Heath, William, 1795-1840 (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
This Statue of Roman Cement has been erected at the cost of 40?s Freeholders.
1 print : col.
Keywords: Caricatures; Cartoons; Catholic emancipation; O'Connell, Daniel, 1775-1847; Wellington, Arthur Wellesley, Duke of, 1769-1852